N-Aryl-5-aminopyrazole: A Versatile Architecture in Medicinal Chemistry - Marinozzi, Maura; Marcelli, Gloria; Carotti, Andrea (Mini Reviews in Medicinal Chemistry, 2015)
N-Aryl-5-aminopyrazole represents a key structural motif in a plethora of biologically active molecules endowed with a wide spectrum of pharmacological properties. Accordingly, this scaffold can be certainly included in the category of a privileged structure. As an example, N-aryl-5- aminopyrazole along with its 5-ureido derivatives are recurrent scaffolds in the field of inhibition of the different members of mitogen-activated protein kinases (MAPKs). Over the past recent years a large number of papers highlighting the design, synthesis and biological evaluation of different classes of N-aryl-5-aminopyrazole-containing compounds have been reported in the literature, but a review on this topic is still missing. With the aim to fill this gap, the present review article focuses on the recent developments (1995-mid2014) on the application of the N-aryl-5-aminopyrazole-based compounds in different therapeutic fields, with a particular attention to the design and structure-activity relationships (SAR) aspects of each class of compounds.
Keywords: privileged structure